Traditional healing beliefs and practices in Bagnibari and Samair villages: implications for public health in rural Bangladesh - Camp, Lauren Ashley; Pervin, Jesmin; Raza, Farrukh (BRAC University, 2016)
Includes bibliographical references (page 80-81).